BIODIVERSITY OF ONION CROPS: AFLATUNSKIY ONION (ALLIUM AFLATUNENSE B. FEDTSCH.), COMPOSITION OF ELEMENTS - T. M. Seredin; A. F. Agafonov; L. I. Gerasimova (Овощи России, 2016)
The evaluation of aflatunskiy onion for accumulation level of 25 elements was done. It was found that this crop is a source of potassium, calcium, and phosphorus. It is able to accumulate iodine, magnesium, zinc, ferric, silica. The obtained data shows the nutrition value of the genus of Allium L.